Analisis Kesadaran Metakognitif Mahasiswa Jurusan Tadris Biologi terhadap Pembelajaran Biologi di IAIN Kerinci - Angraini, Lola; Juita, Dewi; M, Yusmaridi (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2021)
Metacognitive awareness is indispensable for successful learning, considering metacognitive awareness allows students to be able to manage cognitive skills and be able to see their weaknesses, so that improvements can be made in subsequent actions. The development in the 21st century demands that everyone be aware of the importance of metacognition. This study aims to analyze the metacognitive awareness of students towards learning biology in the Biology study program and to determine the level of metacognitive awareness of biology students at IAIN Kerinci in class A and B semester 3. Data collection using questionnaires or questionnaires and interviews. The descriptive data analysis technique was categorized into two, namely the metacognitive awareness interval and the metacognitive awareness percentage. The results of this study indicate that: (1) Each indicator of metacognitive awareness is measured using the Metacognitive Awareness Inventory (MAI), where each point of the indicator is different. The categorization of metacognitive awareness is divided into 5, namely very good, good, moderate, low, and very low. (2) The percentages for metacognitive awareness of Biology students in the third semester are as follows: in class A there are 3 (very low), 4 (low), 4 (moderate), and 1 (good). Whereas in class B there are 1 (very low), 11 (low), and 4 (moderate). (3) The results of the metacognitive awareness interview of Biology students in semester 3 showed that each individual has different metacognitive awareness, and of course understands a different material.